Transparency of Regulation and Cross-Border Bank Mergers - Matthias Köhler (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2008)
Although there is anecdotal evidence that merger control may constitute a barrier to the integration of European retail banking markets, systematic empirical evidence is missing until now. This paper aims to fill this gap. Based on a unique dataset on the transparency on merger control in the EU banking sector, we estimate the probability that a bank is taken over as a function of its characteristics, country characteristics and the transparency of merger control in the banking sector. The results indicate that a bank is systematically more likely to be taken over by foreign credit institutions if the regulatory process is transparent. Particularly large banks are less likely to be taken over by foreign credit institutions if merger control lacks transparency. This is in line with the hypothesis that governments may block crossborder bank merger because they want the largest institution in the country to be domestically owned. Domestic mergers are not affected. This suggests that merger control may therefore constitute an important barrier to cross-border consolidation and that further integration of EU banking markets requires a higher degree of transparency of the regulatory process.
More recent version: http://hdl.handle.net/10419/29646
Keywords: 330; Fusionskontrolle; Internationale Bank; Übernahme; Fusion; EU-Staaten